Transformative Service Research and the role of service robots: a bibliometric analysis - Priscila Pasti Barbosa; Felipe Facco Mendes Ferreira; Larissa Cayla Cesário; Glauco Henrique de Souza Mendes (Gestão & Produção)
Abstract Robotic Transformative Service Research (RTSR) is an interdisciplinary field expanding the principles of Transformative Service Research (TSR) by integrating service robots into contexts focused on improving well-being and reducing vulnerabilities. Despite its relevance, RTSR literature remains fragmented across domains like healthcare, robotics, and service management, hindering a cohesive understanding of the field. This study addresses this gap through a systematic review and bibliometric analysis of RTSR, identifying thematic trends, research gaps, and future directions. The central objective is to map RTSR’s intellectual structure using bibliographic coupling, which grouped 152 articles into six thematic clusters. Data was collected from academic databases and analyzed through network mapping. The use of service robots in elderly care stands out for providing emotional well-being, inhibiting loneliness, for example. The analysis of several use cases of service robots in elderly care is carried out in the article to highlight the importance of using this service in cases of great importance, such as in cases of dementia. Cultural sensitivity and personalization of robots emerged as essential factors for increasing user acceptance and scalability, particularly in diverse healthcare environments. Ethical concerns, such as emotional dependence from long-term interaction with robots, are also discussed, especially in long-term care, where robots serve as emotional companions. This paper proposes a research agenda focused on interdisciplinary integration and the development of cultural competence to expand the use of service robots. The analysis of RTSR literature identifies key challenges and outlines paths to advance the application of these robots across different sectors.